(untitled) (AYUSHDHARA, 2017)
Change in life style has resulted in the increased production of free radicals in the body which not only raise the oxidative stress but also plays an important role in the immune system dysfunction. Now a day, human body is continuously exposed to different types of agents that result in production of reactive species called as ‘free radicals’. Diabetes is a group of metabolic diseases characterized by high levels of blood sugar (hyperglycemia). Many evidences from experiments have proved that free radicals and oxidative stress play a major role in complications of Diabetes mellitus like coronary heart disease, Neuropathy, Nephropathy, Retinopathy and stroke. In Ayurveda, the syndrome Diabetes mellitus has been covered under the broad heading of Prameha. Rajata Yoga is mentioned in Rasa Tarangini and indicated in all types of Prameha. Rajata bhasma, Twak churna, Ela churna and Patra Churna are the main ingredients of Rajata Yoga. The aim of present study is to evaluate the in vitro anti oxidant activity of Rajata bhasma & Rajata Yoga. The method followed to evaluate the anti oxidant activity is 1, 1- diphenyl 2- picrrylhydrazyl (DPPH) radical scavenging assay has been used in the determination of In- vitro antioxidant activity. Results: Significant Inhibition percentage of Rajata bhasma & Rajata Yoga was seen in increasing order of percentage when sample concentration (100µl, 200µl, 300µl, 400µl, 500µl) was increased. Rajata bhasma showed 69.86% of inhibition and Rajata Yoga showed 80.10% of inhibition in 500 µl sample concentrations respectively.